2022
DOI: 10.1002/jac5.1737
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of discharge medication discrepancies resolved by pharmacists at a veterans affairs teaching hospital

Abstract: Introduction Although reassuring outcome data exist, not all pharmacist discharge efforts have been effective. This may be explained by heterogenous medication reconciliation definitions and processes. At a Veterans Affairs Teaching Hospital, Clinical Pharmacy Specialists (CPS) review the discharge medication reconciliation as part of a multidisciplinary process. The objective of this study is to describe CPS' role in resolving discharge medication reconciliation discrepancies and to evaluate potential patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…More than half of patient discharges contained at least one error, thus emphasizing the need for PMRD to better optimize patient safety. The results of this study align with previous studies in demonstrating decreases in medication discrepancies and harm reduction from pharmacist involvement in the discharge process 4,10,14 . Similar to Muller et al, our internal medicine teaching services commonly serve an older patient population with multiple comorbidities, who on average have 12 medications upon admission and an average Charlson Comorbidity score of 5.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…More than half of patient discharges contained at least one error, thus emphasizing the need for PMRD to better optimize patient safety. The results of this study align with previous studies in demonstrating decreases in medication discrepancies and harm reduction from pharmacist involvement in the discharge process 4,10,14 . Similar to Muller et al, our internal medicine teaching services commonly serve an older patient population with multiple comorbidities, who on average have 12 medications upon admission and an average Charlson Comorbidity score of 5.…”
Section: Discussionsupporting
confidence: 88%
“…However, these studies did not further assess the unintentional discrepancies that were identified, leaving a gap in understanding their potential for patient harm. While Muller et al 10 have evaluated potential patient harm avoided through pharmacist intervention in resolving discharge medication reconciliation discrepancies, there remains a need for further investigation into the financial implications of such interventions.…”
Section: Introductionmentioning
confidence: 99%